Peran Kualifikasi Guru dalam Meningkatkan Prestasi Belajar Siswa di MI Kalifa Nusantara Tahun Pelajaran 2019/2020 - Ratih, Dewi; Soedjiwo, Novena Ade Fredyarini; Libriyanti, Yuyun (STAI Denpasar Bali, 2022)
This research was motivated by all teachers in MI Kalifa Nusantara have met academic qualification standards. However, it seems that the teacher’s academic qualifications have not been able to maximize the student’s learning achievement. This is evidenced by a decrease in learning achievement. The purpose of this research is to know qualifications teachers in improving student learning achievement and the inhibitory and supporting factors faced by teachers in improving student learning achievement at MI Kalifa Nusantara Years lesson 2019/2020. This study uses a qualitative approach, with a qualitative interpretive method. Determination of the informant was done by purposive sampling. The data collection techniques was by observation, interviews, and documentation. The results of the study revealed that, the role of teacher qualifications is improving learning achievement is determined by academic and non-academic qualifications, learning planning qualifications, learning process qualifications, personality qualifications, and learning process results through evaluation. While the supporting factors of learning achievement internally are student intelligence, internal motivation, as well as interests and talents. The external support factors are parental motivation, adequate facilities, out-of-school tutoring, and teacher rewarding. The inhibitory factor of learning achievement consists of internal factors, namely lack of motivation and interest in learning. Meanwhile, the external factor is the lack of attention from parents, students not taking additional lessons outside of school, and less supportive facilities.